Предмет: Алгебра,
автор: daschenka26
1) (х+2)(х²-2х+4)-х(х-3)(х+3)=26
2) (х-3)(х²+3х+9)-х(х²-16)=21
Пожалуйста помогите решить уравнение
Ответы
Автор ответа:
0
(х+2)(х²-2х+4)-х(х²-9)=26
х³+2³-х³+9x=26
2³+9x=26
8+9x=26
9x=18
x=2
(х-3)(х²+3х+9)-х(х²-16)=21x³-3³-x³+ 16x=21
27+16x=21
16x=21-27
16x=-6
нет корней
х³+2³-х³+9x=26
2³+9x=26
8+9x=26
9x=18
x=2
(х-3)(х²+3х+9)-х(х²-16)=21x³-3³-x³+ 16x=21
27+16x=21
16x=21-27
16x=-6
нет корней
Автор ответа:
0
1) (х+2)(х²-2х+4)-х(х-3)(х+3)=26;
X³-2x²+4x+2x²-4x+8-x³-3x²+3x²+9x=26;
9x=19
X=2.
2) (х-3)(х²+3х+9)-х(х²-16)=21;
X³+3x²+9x-3x²-9x-27-x³+16x=21;
-27+16x=21;
16x=48
X=3
Похожие вопросы
Предмет: Қазақ тiлi,
автор: Аноним
Предмет: Химия,
автор: NdndnN
Предмет: Литература,
автор: Аноним
Предмет: Математика,
автор: olenka151083
Предмет: Информатика,
автор: Аноним